2019
DOI: 10.7191/jeslib.2019.1171
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing Historical Scientific Data: A Case Study Involving Fruit Breeding Data

Abstract: The objective of this paper is to illustrate the importance and complexities of working with historical analog data that exists on university campuses. Using a case study of fruit breeding data, we highlight issues and opportunities for librarians to help preserve and increase access to potentially valuable data sets. Methods: We worked in conjunction with researchers to inventory, describe, and increase access to a large, 100-year-old data set of analog fruit breeding data. This involved creating a spreadshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although digitization is seen as a way to preserve analog datasets and increase their accessibility, scanning old data is known to be both time and resource intensive (Bosilovich et al 2013;Farrell et al 2019). Yet, more than 40% of our survey respondents have done some scanning, illustrating their commitment to preserving the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although digitization is seen as a way to preserve analog datasets and increase their accessibility, scanning old data is known to be both time and resource intensive (Bosilovich et al 2013;Farrell et al 2019). Yet, more than 40% of our survey respondents have done some scanning, illustrating their commitment to preserving the data.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the data may be able to be ingested into data repositories, some may be able to be scanned and placed into digital repositories, some could possibly be added to archives in its analog format, and other analog datasets may be able to be indexed and identified via a registry. A case study that investigated how to organize, preserve, and make a historical fruit breeding analog dataset discoverable implemented a variety of these strategies (Farrell et al 2019). For other data sets, a different combination of methods might be more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic data generated for selected germplasm since 2013 (Monteverde et al., 2018; Rosas et al., 2018) have also been stored separately from phenotypic records. This scattering and disconnection of IRBP data poses potential risk of data loss, underuse (Farrell et al., 2019), and mismatches that may negatively impact on selection accuracy and program efficiency (Rutkoski, 2019). A crucial step for a proper data management system is the consolidation of a unified database combining phenotypic information from multiple trials, years, and locations with genomic and pedigree records (Odell et al., 2017), and store the data in a centralized location.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in this topic began when a few senior faculty members approached the University library for assistance in organizing and possibly housing their analog data (Farrell et al 2019). A survey of life sciences researchers on campus revealed that many held analog data and considered it valuable but were unsure of how to preserve it (Farrell et al 2020).…”
Section: Introductionmentioning
confidence: 99%